The Pathogenesis and Prevention Strategies of Radiation-Induced Brain Injury - Wang Y; Wu J; Wang Y; Song W; Ren H; Han X; Dong X; Guo Z (Cancer Management and Research)
Yong Wang,1,* Jun Wu,2,* Ya Wang,1 Weiyuan Song,3 Hongjian Ren,4 Xu Han,5 Xiaoqi Dong,6 Zhiqiang Guo1 1Oncology Department, Shanxi Fenyang Hospital, Lüliang City, Shanxi Province, People’s Republic of China; 2Nuclear Medicine Department, Shanxi Fenyang Hospital, Lüliang City, Shanxi Province, People’s Republic of China; 3Nephrology Department, Shanxi Fenyang Hospital, Lüliang City, Shanxi Province, People’s Republic of China; 4Tumor Radiotherapy, Shanxi Fenyang Hospital, Lüliang City, Shanxi Province, People’s Republic of China; 5Anesthesiology Department, Shanxi Fenyang Hospital, Lüliang City, Shanxi Province, People’s Republic of China; 6Pharmacy Department, Shanxi Fenyang Hospital, Lüliang City, Shanxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiqiang Guo, Email sxguozhiqiang@163.comAbstract: Radiation-induced brain injury (RBI) encompasses the severe symptoms resulting from radiation-induced damage to the normal tissue surrounding tumors in patients undergoing radiotherapy for head and neck malignancies. The primary symptoms include skin erythema, pain, and may extend to headache, syncope, nausea, vomiting, memory impairment, alterations in mental status, visual disturbances, drowsiness, and other neurological abnormalities localized to the area of treatment. These side effects both limit the effectiveness of radiation therapy and reduce the patient’s quality of life. During radiotherapy, while killing tumor cells, the radiation will damage the cerebral microvascular endothelial cells, cause cerebrovascular inflammatory response, destroy the blood-brain barrier, aggravate the cerebral oxidative stress response, and induce apoptosis of nerve cells. This review summarizes the mechanisms underlying the occurrence and progression of radiation-induced brain injury and discusses promising strategies for prevention and treatment that may be applicable to clinical patients suffering from this condition.Keywords: radiation-induced brain injury, radiation protection agents, oxidative stress, apoptosis, cognitive function